Dry Powder Compaction under Ultrasonic Action to Shape Nanostructured Bulk Materials; "EUROMAT-Congress", Prague, september 5-8, 2005 - Khasanov O. L. Oleg Leonidovich (2005, 2005)
To obtain required complex shape of the articles the method of dry powder compaction under ultrasonic action was developed. The process was performed in a die which was an acoustic wave-guide and setting of the ultrasound amplitude comparable with the mean size of the powder particles or agglomerates was carried out. It essentially decreases the stress gradients in a green compact, interparticle and wall friction and as a result provides the uniform distribution of density, which leads to sintering qualitative articles having required shape and tolerances. The method can assure the nano-scale microstructure of the green compact from nanopowder to sinter nanostructured bulk material. Any binders and consequently wet processing stages were eliminated. The method was used for compaction of different nanopowders and common powders: zirconia, alumina, ferroelectric (Ba,Sr)TiO3, dielectric (Ba,W)TiO3, piezoelectric (Pb,Zr)TiO3, (Pb,La)TiO3, superconducting YBa2Cu3O7, composite Al2O3-Fe, metal Cu, etc., to manufacture a lot of articles for structural and functional purposes